P300 and extraversion in the visual odball paradigm - Tatalović Vorkapić, Sanja (Array, 2010)
The aim of this study was to investigate the relationship between P300, evoked by a standard visual oddball paradigm, and extraversion measured by the Eysenck Personality Questionnaire (EPQ-RA). The sample consisted of 54 subjects, all female, right-handers, in the age range 19-23 years. P300 was measured using occipital and parietal electrodes in two repeated trials for each subject. Regardless of the trial block, the electrode site effect was significant for both latencies and amplitudes. A tendency towards lower P300-amplitudes emerged in the second trial, implying a habituation effect. Subjects with higher extraversion showed significantly shorter P300-latencies recorded on the parietal group of electrodes (P3 and P4). However, as a more prominent relationship in the same direction was determined between the extraversion subtrait adventurousness and P300-latency, the effect of extraversion could be mainly attributable to adventurousness. The findings are discussed in terms of arousal theory and task demands.